Culprit and victim: Scenarios for Philippine agriculture amidst climate change - Ivory Myka R. Galang; Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2024)
The study explores the complex role of Philippine agriculture, both as a contributor to and a victim of climate change. The agriculture sector, responsible for 23 percent of the country's greenhouse gas (GHG) emissions, simultaneously faces severe losses from extreme climate events, accounting for 60 percent of disaster-related damages. This study aims to assess the impact of climate change on Philippine agriculture, evaluate mitigation and adaptation options, and formulate effective policy recommendations to foster resilience and sustainability. Scenarios are analyzed using a computable general equilibrium model to examine different pathways for adapting to and mitigating climate change impacts on agriculture, framed as a) baseline; b) intensified adaptation; and c) combined adaptation and mitigation scenarios. The findings reveal that without enhanced interventions, Philippine agriculture is at risk of long term supply and consumption reductions, and therefore greater vulnerability. Meanwhile, adoption of intensified adaptive and mitigation measures shows potential for improved resilience, increased productivity, and contributions to national climate commitments, at fairly modest intervention costs. The policy recommendations emphasize proactive climate action in agriculture that aims to enhance adaptation while contributing to mitigation efforts. Accurate GHG emissions estimates across sectors, especially agriculture, are crucial for targeted policies. Climate adaptation measures must be prioritized to ensure sustainable production amid growing climate risks, despite potential uneven outcomes across sub-sectors. Introducing cost-effective mitigation technologies, such as Alternate Wetting and Drying for rice and improved manure management, can reduce emissions without compromising productivity. The Philippines should integrate agriculture into its unconditional Nationally Determined Contributions (NDC), focusing on technologies that offer sustainability while maintaining sectoral competitiveness and food security.
Keywords: 330; climate change; Philippine agriculture; mitigation; adaptation; greenhouse gas emissions; GHG; nationally determined contributions; sustainable farming; resilience; climate-smart agriculture; food security; emission reduction; alternate wetting and drying; manure management; climate adaptation policy; agricultural sustainability; Department of Agriculture; climate change expenditure tagging; Climate Change Commission; Paris Agreement